(untitled) (Archives of Criminology, 1964)
Problems of reactive mental disorders and of the simulation of mental disorders have lately been very poorly represented in both psychiatrist and criminological literature. The present contribution discusses the sources of a considerable number of difficulties which emerge in practice when discussing the question of “Reactive disorder or malingering?”, as well as the errors of diagnosis in diagnosing malingering. The contribution is based on a analysis of material which comprizes three hundred and fifty cases of reactive mental disorders, and ninety-nine cases of malingering (simulation), with the accused; such material has been obtained from the Department of Forensic Psychiatry of the Psychoneurological Institute and from fifteen mental hospitals in Poland, to which prisoners were sent for observation. When making use of the term of “ malingering” , the contents of that notion ought to be narrowed down so as to comprize behaviour of such kind, which consists in an individual who is not mentally ill consciously producing definite psychopathological symptoms. We could not possibly consider to be malingering in the true sense of the word the producing by a mental patient (e.g. one suffering from schizophrenia) of symptoms which are not characteristic of the disorder in question. What is described by the term of sursimulation, even though it contains elements of malingering, essentially differs from true malingering. On the other hand, the view is not correct which reads that we may only then speak of malingering, when the simulating of symptoms of mental disorders makes its appearance with persons who do not exhibit any abnormal traits. Malingering most frequently makes its appearance with prisoners who exhibit symptoms of psychopathy, encephalopathy, mental deficiency, etc. The problem of metasimulation deserves special attention. The fact that at a given moment we have to do with a behaviour which indicates malingering is not by itself evidence that previously, during the period immediately preceding such malingering, reactive disorders did not appear with same prisoner. The symptoms of reactive disorders during the period which preceded the sending of the prisoner to a mental hospital may have become almost entirely extinguished, while their place was taken by an attitude of malingering, greatly reminiscent of the recent symptoms of reactive mental disorders. Besides, in cases of that kind there also arises, as a rule, the question of whether, side by side with elements of malingering, there do not appear feebly marked symptoms of reactive mental disorders, as remnants of the reactive disorders from which the patient had previously been suffering. Neither should another difficulty, which jurisdiction finds in its path, be forgotten. When having to do with an attitude of obvious malingering, one ought to take into consideration the possibility of malingering being gradually transformed into reactive disorders. The mechanism of malingering becomes fixed in the prisoner’s mind, it undergoes automation, and sets into motion a hysterical mechanism, which, in its turn, acts independently, in the way proper to it, owing to which psychogenic disturbances arise. Such a state as that cannot be described as malingering, in spite of the fact that it was simulation that not only constituted the starting-point of the disorders arisen, but had actually provoked, and to some extent moulded, them. An individual in that state no longer exercises any control over the symptoms of reactive disorders which have appeared, he ceases to exercise any mastery over them; the former malingering mechanism has been driven out of his consciousness and has become transformed into a new, and considerably more complicated hysterical mechanism. The cases discussed above may still run a course complicated in another way, namely after the transformation of malingering into reactive disorders certain symptoms of the latter in their turn are subject to undergo, even after the extinction of the disorders, a conscious consolidation through the new manifestation of the malingering mechanism. Therefore in such cases malingering may be observed, not only at the beginning, but also after the recession of the state of reactive disorders, in the form of metasimulation. The mechanism of the arising of reactive disorders is analogous to that of the arising of malingering; at the basis of both the above mechanisms there lie certain common fundamental tendencies. In all probability malingering runs along the very same tracks as hysterical reaction, and mobilizes, through the intermediary of autosuggestion, analogous mechanisms, causing, as it were, the automation of certain attitudes. Malingering individuals, even though at first they control that mechanism and consciously steer it, may lose their control over it. This leads to the cases of a transformation of malingering into reactive mental disorders, discussed above. The knowledge of making use of a mechanism approximating a hysterical one, of producing and fixing certain symptoms which would constitute a good imitation of disorders, is — as is well known — a most difficult thing. This is why long-lasting and consistently carried out malingering is an extremely rare phenomenon. An individual who simulates in such a way must be equipped with peculiar features, in order to be equal to tasks of that kind. Hence the well-know saying that “ one can simulate well only that which is close to the simulating persons’s individuality” (Lassegue), and that “ a good malingerer must be born such” (Braun). Among psychiatrists there prevails, generally speaking, an agreement as to the view that long-lasting and consistent malingering happens, as a rule, only with persons whose personality exhibits clearly pathological features. The data obtained from sixteen mental hospitals for the period of 1953 — 1960 bear witness to the fact that, out of 5,967 male prisoners sent there for psychiatric examination, mental reactive disorders have been found to exist with 711 cases (11.9 per cent.), and malingering of mental disorders in a mere 99 cases (1.6 per cent.). In the case of the 793 women, sent from prisons to mental hospitals for psychiatric examination, reactive disorders were found to exist in 73 cases (9.2 per cent.), and malingering in a mere 7 cases (0.9 per cent). When we analyse the 99 forensic-psychiatric reports which diagnosed malingering, it appears that we may distinguish two different groups of cases among them. The first of them comprizes 70 prisoners, with whom the diagnosis of mere malingering does not arouse any essentia] diagnostical reservations. On the other hand, in the second group, which comprizes 29 cases, we have to do with 19 cases of undoubted metasimulation, as well as with 19 cases which are doubtful. Doubts arise in connection with the possibility of the co-existence of reactive disorders with simulation (5 cases), as well as with the presence of reactive disorders during the period immediately preceding malingering (3 cases), or finally, because of data which speak in favour rather of reactive disorders than of malingering (11 cases). Thus it is only in seventy cases that the diagnosis of malingering does not arouse any serious doubts; neither should it be forgotten that, at the same time (i.e. during the same seven-and-a-half-year period) as many as 711 cases of reactive mental disorders were observed with prisoners in sixteen mental hospitals. Thus cases of malingering of long duration are an extremely rare phenomenon in forensic psychiatrist practice. For the purpose of establishing how do the data look which concern long-term malingering of mental disorders in prisons, data concerning the number of cases of malingering within the period of one year have been obtained from the psychiatrists employed in two large Warsaw prisons, which are, in principle, destined only for prisoners under investigation. It was found that the number of malingering prisoners amounted, in one prison to nine, and in the other to five. Taking into consideration the number of all the prisoners detained in those prisons in the course of twelve months, the “ co-efficient of malingering” , calculated as per one thousand prisoners, amounts to 1.86 and 0.96 respectively. After a correction has been introduced, because of the possibility of certain prisoners failing to report for examination, that co-efficient should not exceed 2 pro mille.[1] Among the 350 cases of reactive disorders, selected by lot out of the total number of reports with a diagnosis of “ reactive disorder” for the purpose of obtaining a representative sample, metasimulation during the period of clinical observation has been stated to take place in as many as 24.8 per cent, of the cases. When examining the two groups of cases: those of “ pure” malingering and those of metasimulation, we can establish the essential differences which exist between them. Those prisoners with whom no reactive disorders have been found to exist during observation, simulate other symptoms of psychotic disorders than those prisoners, with whom malingering has made its appearance only after the extinction of reactive disorders in hospital. In the group of the seventy “ pure” cases of malingering the most numerously represented is the simulation of memory defects and of mental deficiency, or else of dementia; apart from the above, prisoners also simulate symptoms of conversion hysteria, of hallucination or delusion, as well as, exceptionally, symptoms of stupor. On the other hand, in the group of fifty cases of metasimulation, more than one-half of the total number consisted of prisoners who simulated symptoms of pseudodementia along with elements of puerilism (which were altogether absent from the group of “ pure” simulation). Of cases of con- fabulation with symptoms of pseudodelusions there were eight, while there were none of them in the “ pure simulation” group. Of individuals who simulated memory disorders there were three times less. Deserving of particular attention are the twenty-six cases of “ pure” malingering, in which the whole manner of simulating, the contents of the pseudo-symptoms produced, and the prisoner’s entire behaviour are of such a kind, that it seems improbable that the simulating individual could suppose that he would succeed in deluding his environment. The attitude of such prisoners is one of playful contradiction, usually coupled with irony and mockery with regard to the medical personnel; their behaviour is characterized by elements of acting and indeed of clowning; the absurdity of their utterances is glaring. Periodically, however, states of a certain inhibition make their appearance, and from time to time sudden changes of mood are visible, considerable tension, violent attempts at aggressive behaviour, and tendencies to self-mutilation. It was Mönkenmöller who, once upon a time, drew attention to that peculiar form of malingering, in which it is impossible to detect any intelligible purpose. In such cases malingering assumes the character of acting which gives the malingerer some satisfaction (“spielerische Simulation’ 4, as Utitz called it); The picture of malingering gives one to think by its specific features, and is distinguished, from the other types of malingering, by its altogether exceptional primitivism and inconsistency. 92 per cent, of the prisoners who simulated in that way were recidivists with a considerable number of previous convictions to their names. In the anamnesis of nearly one-half of them alcoholism and brain trauma, as well as other chronical brain diseases, made their appearance. More than one-half of their total number have performed self-mutilation in prison. In the cases of “pure”, true malingering there appear, in the hospital material investigated, numerous prisoners with symptoms of encephalopathy (37.1 per cent.) and psychopaths (about 40 per cent.), as a rule described as impulsive, irritable, aggressive. Not a single malingering prisoner has been qualified as an individual with a normal personality. The prisoners who simulated mental disorders are recruited — 81 per cent, of them — from among recidivists, as a rule from among juvenile or young offenders: sixty-six per cent, of the investigated were under twenty-five years of age. They belonged to the category of offenders who commit common offences, mostly offences against property, with thefts predominating. Among the reactive mental disorders to be met with in forensic psychiatrist practice and in the prisons, two kinds of disorders may be distinguished. First of all, the group of disorders of the type of hysterical disorders, the majority of which has a more primitive character; they are: pseudodementia, Ganser’s syndrom, puerilism, states of incomplete stupor and of stupor, fancies with contents similar to those of delusions, and symptoms of conversion hysteria. It is precisely that category of disorders that oftentimes causes particular difficulties in practice, when it is a matter of distinguishing them from malingering. The second group of reactive disorders, with more psychotic symptoms, comprizes: reactive depressions, stupor, and syndroms with delusions and hallucinations and paranoid states. In this category of disorders disturbances of consciousness are much more clearly discernible than they are in the first. Bunyeyev, however, correctly emphasizes the fact that clinical experience points to the fact that in the several syndroms distinguished above there are frequently contained elements, of other reactive syndroms, and, moreover, in a considerable number of cases it can be observed, how, in the course of the disorders, one set of syndroms gives way to other symptom syndroms. Consequently, the clinical picture is usually considerably more complicated than would result from a description that would only take into consideration the most fundamental elements. Among the three hundred and fifty cases of reactive disorders with prisoners under investigation the several syndroms make their appearance In the following dimensions: Pseudodementia 90 cases 25.7 per cent. Puerilism 16 “ 4.6 per cent. Ganser’s syndrom 17 “ 4.9 per cent. Depressions 79 “ 22.6 per cent. Syndrom of stupor (41) 59 “ and states of incomplete stupor (18) 47 “ 16.9 per cent. Syndroms with hallucinations and delusions 13.4 per cent. Paranoid states 12 “ 3.4 per cent. Conversion hysteria 20 “ 5.7 per cent. Fancies with contents similar to delusions 10 “ 2,8 per cent. Pseudodementia, Ganser’s syndrom and puerilism between them account for 35.2 per cent, of the material investigated. Pseudodementia and puerilism frequently constitute the source of serious difficulties when it is a matter of distinguishing them from malingering, if hospital observation is of too short duration. Seventy per cent, of the above cases spent over three months on observation in hospitals, including nearly twenty per cent, who spent more than six months there. After a syndrom of pseudodementia, it may be sometimes observed the malingering of the extinct symptoms of that syndrom (metasimulation). Among the cases of metasimulation in the material under investigation in fifty-five per cent, malingering was precisely connected with pseudodementia. Reactive depressions are the second set, as far as numbers are concerned, in the material under investigation (22.64 per cent.). Reactive depressions are of various character. The obvious colouring of the majority of such states with hysterical traits frequently lends a peculiar stamp to the clinical picture, and may incorrectly suscitate a suspicion of malingering. Mental disorders with a stupor syndrom, as is well known, rarely arise as isolated type of reaction. Considerably more frequently stupor takes place after pseudodementia, Ganser’s syndrom and puerilism, not infrequently after a period of a seeming withdrawal of all reactive symptoms. What is more, after stupor there frequently appear once more symptoms of other reactive disorders, first and foremost those of pseudodementia (Bunyeyev, Pastushenko). In cases of incompletely developed stupor there frequently appear suspicions of malingering, even though such casses ought to be numbered undoubted mental disorders. When discussing cases with a hallucination and delusion syndrome one ought to remember that even in such cases the suspicion of malingering occasionally makes its appearance. This is influenced by the fact that the contents of the hallucination are closely connected with the prisonner’s own situation, that his behaviour is characterized by lively emotional reactions, and that he not infrequently manifests interest in his further lot, his family, etc. In fact the suspicion of malingering as a rule proves to be unfounded. Morever, it should not be forgotten that, in cases with a hallucination and delusion syndrome there not infrequently emerge serious diagnostic difficulties in connection with the posibility of the existence of schizophrenia. Among the reactive disorders observed with prisoners in the hospitals there were twelve cases of acute paranoid state. In this, relatively very infrequent, syndrom, which develops against a background of intensified fear and anxiety, and rapidly disappears under conditions of hospitalization, the existence of hallucinations, mainly visual ones, has also been found. The symptoms which approach delusions include the so-called confabulation, with contents resembling those of delusions (“wahnhafte Einbildungen” ), which had been described by Birnbaum more than fifty years ago. The inventing of occasionally the most improbable and queerest facts takes place against a background of usually glaringly expressed hysterical traits; occasionally elements of pseudodementia and puerilism become visible. All this together may suscitate serious suspicions of malingering; prolonged observation, however, makes it posible to find the existence of clearly reactive disorders. Of such cases there were ten in the material under investigation. Predominant among them were cases of persecutory pseudodelusions (eight cases), with the most absurd and fantastical subject-matter. In the remaining two cases it was grotesque grandiose pseudodelusions that made their appearance. Both the attitudes and the behaviour of all such individuals were, as a rule, in complete contradiction with the contents of their utterances. Those prisoners who exhibited symptoms of reactive mental disorders differ in an essential way from those prisoners who simulate pathological symptoms. First of all, there are considerably less recidivists among them: the percentage of the latter did not exceed 33 per cent, while with the simulators it reached 81 per cent. Among the prisoners with reactive disorders there are less individuals who would exhibit organic changes of the brain (23 per cent., as compared with 37,1 per cent, with the malingerers), while, on the other hand, the percentage of persons of the schizoid type is considerably larger (36 per cent., as against about 10 per cent, with the malingerers), as well as that of psychopaths with obvious hysterical traits (31.4 per cent., as against about 20 per cent, with the malingerers). A mere 4.5 per cent, of the total number of prisoners with reactive mental disorders under investigation were found to be persons whose premorbid personality did not suggest any suspicions concerning pathology; all the remaining ones figure, in the diagnoses, either as psychopaths, or else as persons with symptoms of encephalopathy. In spite of the lack of any exhaustive anamneses in a great many cases it was found possible to state that at least 17 per cent, of the prisoners sent to mental hospitals because of reactive mental disorders had already previously suffered from such disorders. The cases of reactive states of a protracted character, numerous in the material under investigation (32 per cent, among the cases dealt with in the Institute of Psychoneurology) make one realize the importance of a proper conception of the problem of reactive mental disorders with prisoners. In those cases states which could at first produce an impression of simulation were relatively numerously represented. Mistrust in such cases might well be increased by the fact that nearly one-half of them consisted of prisoners accused of the perpetration of homicide. A hospital observation which went on for many months on end, not only did confirm the diagnosis of a reactive mental disorder, but has also, over and above that, demonstrated that those mental disorders had, in a considerable number of cases, become so deep, that a large number of the patients had to be assigned for release from prison. Merely about 22 per cent, of the total of those suffering from protracted disorders recovered their health and could, later on, be prosecuted before a law-court. A working hypothesis in both prisons and forensic-psychiatric practice should therefore be the premisse that a pure malingering of mental disorders going on for a longer period of time is an altogether exceptional phenomenon, and that, as a rule, we have to do, in such cases, with reactive disorders. A different approach not only does run counter to the present-day state of psychiatrist knowledge, but is also highly harmful for both forensic and prison practice, as well as being inhumanitarian. [1] In order to avoid any misunderstandings it ought to be emphasized that we are here referring to cases of long duration, of a malingering of mental disorders going on for at least several weeks on end. Clumsy attempts at simulating pathological symptoms for a period of a few days, naturally, altogether elude a psychiatrist who is not permanently employed in the prison in question, and, in all probability happen much more frequently